Urinary metabolites as biomarkers of dietary intake: a systematic review - Jackson, Mariah Kay; Wang, Bing; Rasmussen, Heather; Natarajan, Sathish Kumar; Bilek, Laura D.; Ehlers, Diane K.; Graeff-Armas, Laura; D’Angelo, Christopher; Cochran, Teresa; Harp, Kimberly; Hanson, Corrine (Frontiers in Nutrition, 2025)
BackgroundCurrent diet assessment tools, such as food frequency questionnaires, may result in misclassification bias from measurement error and misreporting. These limitations can be mitigated by diet-related biomarkers in urine specimens, an emerging approach to characterize dietary intake.ObjectiveWe conducted a systematic review to identify urinary biomarkers with utility in accurately assessing dietary intake, including individual foods and food groups.MethodWe retrieved studies from 2000 to 2022 from databases including Embase, CINAHL, Cochrane, and PubMed. Data extraction from included articles was conducted by two independent reviewers for cross validation. Articles identifying urinary biomarkers in relation to food groups/items with adult populations were included and were evaluated for bias using the Joanna Briggs Institute Critical Appraisal.ResultsA total of 65 articles were included and categorized as biomarkers of fruit (n = 13), vegetables (n = 5), aromatics (n = 5), fruits and vegetables (n = 3), grains/fiber (n = 5), dairy (n = 3), soy (n = 10), coffee/cocoa/tea (n = 9), alcohol (n = 6), meat and proteins (n = 6), nuts/seeds (n = 3), and sugar and sweeteners (n = 4). Results expanded the context to which metabolites of foods were compared across similar and dissimilar food groupings. Plant-based foods were often represented by polyphenols, while others were distinguishable by innate food composition, such as sulfurous compounds in cruciferous vegetables or galactose derivatives in dairy.ConclusionCurrent evidence suggests urinary biomarkers may have utility in describing intake of broad food groups, such as citrus fruits, cruciferous vegetables, whole grains, and soy foods, but may lack the ability to clearly distinguish individual foods. These findings indicate the potential of urinary biomarkers to monitor changes in dietary patterns. The improvement of diet assessment methodology is a key step toward strengthening research data validity and accurately measuring outcomes in chronic disease management.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42022308255, Prospero CRD42022308255.